Impact of an Innovative Market Information System for Pulses in Northern Karnataka - Reddy, B. S.; K. B., Ramappa; B. N., Rajeshwari; Patil, Suresh S. (Indian Journal of Marketing, 2014)
Access to information can be truly empowering and aid decision-making, especially in agriculture. Recently, the government and private agencies initiated few programs for adoption of Market Information Systems (MIS) in the areas of agricultural marketing and agribusiness development in the country. In this context, an attempt was made in this paper to analyze the results of one such innovative project for disseminating market-related information to the pulses growing farmers in the Hyderabad-Karnataka region by taking into consideration the before and after situations. The results revealed that majority of farmers possessed communication assets like television and cell phones, but did not have knowledge about area under crop sown, awareness of quality specification of N-spot exchange, and prices of dals prevailing in the neighbouring markets, even though the formal agencies were distributing information on the same. The results after the project’s implementation proved that majority of the farmers were fully aware of the following: prices of pulses in the market, quality of seeds for sale, fertilizers, manures&micronutrients, and plant protection chemical application while production, and so forth. Majority of the respondent farmers started using the disseminated information to decide which pulses were to be grown and how much area was to be allocated in the process of production decisions; and in case of marketing, when to sell, where to sell, whom to sell, and what quantity was to be sold. The study suggested strengthening the existing formal sources of agricultural extension, including post harvest and marketing management techniques in transfer of technology programmes, and disseminating information using modern information communication technologies.